Analysis Of Marketing Strategies In Increasing Competitiveness In Skinos Medan Beauty Clinic - Selamat; Saskia; Rini Indahwati (LPPM STIE EKA PRASETYA, 2022)
This research was conducted based on the number of industries engaged in the same type of business,which creates intense competition in that market share. Skinos Medan beauty clinic has capital, regular customers and experienced employees, However faced with obstacles in the aspect of management and utilization of the company's internal resources and the clinic also faces various threats from external company factors. This research aims to determine and analyze the marketing strategies that can be carried out by the Skinos Medan beauty clinic to increase the company's competitiveness based on STP analysis (Segmentation, Targeting, Positioning) and SWOT analysis (Strength, Weakness, Threat, Opportunity). In this research, the author uses a qualitative method with data triangulation techniques. For data collection techniques are using the method of observation, interviews, documentation, and questionnaires. For data analysis techniques are using STP analysis, IFAS matrix, EFAS matrix, SWOT diagram and SWOT matrix. Based on the results of STP analysis, Skinos Medan beauty clinic uses single-segment concentration strategy for Concentrated Marketing type of target market with the clinic positioning itself using Quality Positioning style. Furthermore, based on the results of the analysis using the IFAS matrix, EFAS matrix, SWOT diagram and SWOT matrix, the strategy obtained is in quadrant 4 strategy, called a defensive strategy. The implementation of the strategy is thatSkinos Medan beauty clinic will use an alternative WT (Weakness-Threat) strategy to survive and minimizes all the weaknesses and threats of the company.